The Promising Role of Microbiome Therapy on Biomarkers of Inflammation and Oxidative Stress in Type 2 Diabetes: A Systematic and Narrative Review - Paul, Pradipta; Kaul, Ridhima; Abdellatif, Basma; Arabi, Maryam; Upadhyay, Rohit; Saliba, Reya; Sebah, Majda; Chaari, Ali (Frontiers in Nutrition, 2022)
Background: One in ten adults suffer from type 2 diabetes (T2D). The role of the gut microbiome, its homeostasis, and dysbiosis has been investigated with success in the pathogenesis as well as treatment of T2D. There is an increasing volume of literature reporting interventions of pro-, pre-, and synbiotics on T2D patients. Methods: Studies investigating the effect of pro-, pre-, and synbiotics on biomarkers of inflammation and oxidative stress in T2D populations were extracted from databases such as PubMed, Scopus, Web of Science, Embase, and Cochrane from inception to January 2022. Results: From an initial screening of 5984 hits, 47 clinical studies were included. Both statistically significant and non-significant results have been compiled, analysed, and discussed. We have found various promising pro-, pre-, and synbiotic formulations. Of these, multistrain/multispecies probiotics are found to be more effective than monostrain interventions. Additionally, our findings show resistant dextrin to be the most promising prebiotic, followed closely by inulin and oligosaccharides. Finally, we report that synbiotics have shown excellent effect on markers of oxidative stress and antioxidant enzymes. We further discuss the role of metabolites in the resulting effects in biomarkers and ultimately pathogenesis of T2D, bring attention towards the ability of such nutraceuticals to have significant role in COVID-19 therapy, and finally discuss few ongoing clinical trials and prospects. Conclusion: Current literature of pro-, pre- and synbiotic administration for T2D therapy is promising and shows many significant results with respect to most markers of inflammation and oxidative stress.